Synthesis, structure and magnetic properties of cyclic 3d metal clusters based on N–N single bonds of diacylhydrazine ligand. (15th November 2020) - Tang, Qun; Cheng, Ze; Lin, Qingmei; Wu, Jingwei; Zhang, Yan; Zhang, Hongyi; Zou, Huahong; Liang, Fupei
Graphical abstract: The ring dodecanuclear Co12 clusters and double cyclic icosanuclear Mn20 clusters based on N–N single bonds of diacylhydrazine ligand have been synthesized and characterized structurally. Magnetic studies indicate that these high-nuclearity ring clusters exhibit antiferromagnetic interactions. Highlights: Two cyclic high-nuclearity 3d metal clusters were synthesized. Co12 cluster presents a dodecanuclear ring structure consisting of two symmetrical hemicyclic skeletons. Mn20 cluster possesses a double cyclic icosanuclear structure consisting of two deca-nuclear ring skeletons. Magnetic studies reveal antiferromagnetic interaction in Co12 and Mn20 clusters. Abstract: Two cyclic high-nuclearity 3d metal clusters formulated as [Co II 8 Co III 4 (bdsh)4 (Py)12 (MeOH)4 (OAc)4 ]·14CH3 OH·4H2 O (Co12 cluster) and [Mn II 4 Mn III 12 Mn IV 4 (bdsh)10 (Py)2 (DMF)8 (H2 O)8 ]·16DMF·2CH3 OH·8H2 O (Mn20 cluster), (H6 bdsh = N, N' -bis(2-salicylhydrazide)isophthalohydrazide, Py = pyridine, and DMF = N, N' -dimethylformamide), were synthesized by a conventional solution method. The Co12 cluster presents a dodecanuclear ring structure consisting of two symmetrical hemicyclic skeletons bridged with two cobalt ions through the phenolic hydroxyl oxygen atom of H6 bdsh ligand, the hemicyclic skeleton in which five cobalt ions are bridged by four N–N single bonds of diacylhydrazine ligands. The Mn20 cluster exhibits a double cyclic structure comprising of two decanuclear ring skeleton bridged with two phenolic hydroxyl oxygen atoms of H6 bdsh ligands, the decanuclear skeleton in which ten manganese ions are bridged by ten N–N single bonds of five H6 bdsh ligands. Magnetic studies reveal the existence of antiferromagnetic interactions in both Co12 and Mn20 clusters.